Efficacy and safety of palbociclib in patients with estrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer with preexisting conditions: A post hoc analysis of PALOMA-2. (October 2021) - Gelmon, Karen; Walshe, Janice M.; Mahtani, Reshma; Joy, Anil A.; Karuturi, Meghan; Neven, Patrick; Lu, Dongrui Ray; Kim, Sindy; Schnell, Patrick; Bananis, Eustratios; Schwartzberg, Lee
Abstract: Objective: In the PALOMA-2 trial, palbociclib in combination with letrozole prolonged progression-free survival (PFS) and exhibited an acceptable safety profile in patients with estrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer (ABC). This post hoc analysis of PALOMA-2 evaluated the efficacy and safety of palbociclib plus letrozole in patients with preexisting conditions grouped by Medical Dictionary for Regulatory Activities (MedDRA) System Organ Class (SOC). Methods: Postmenopausal patients without prior treatment for ABC were randomized 2:1 to receive palbociclib (125 mg/d on a 3 weeks on/1 week off schedule) plus letrozole (2.5 mg/d, continuous) or placebo plus letrozole. Patients were grouped by the following MedDRA SOC preexisting conditions: gastrointestinal, musculoskeletal, metabolic, and vascular/cardiac. Median PFS was estimated by the Kaplan-Meier method, and treatment emergent adverse events (AEs) were compared between treatment arms within each preexisting condition subgroup. Results: At baseline, 276 (41.4 %) patients had preexisting gastrointestinal disorders, 390 (58.6 %) had musculoskeletal disorders, 259 (38.9 %) had metabolic disorders, and 382 (57.4 %) had vascular/cardiac disorders. Baseline characteristics were similar between subgroups and between each arm within subgroups. Regardless of baseline preexisting condition, palbociclib plus letrozole prolonged PFS compared with placebo plus letrozole. Treatment-emergent AEs associated with palbociclib plus letrozole and dose modifications due to AEs were similar across preexisting condition subgroups. Conclusion: This post hoc analysis of PALOMA-2 demonstrated a favorable effect of palbociclib on PFS and a safety profile consistent with previous observations, regardless of underlying preexisting condition. Pfizer Inc (NCT01740427). Highlights: Preexisting conditions can affect the safety and efficacy of breast cancer therapies. This is a post hoc analysis of patients with preexisting conditions from PALOMA-2. Palbociclib prolonged median PFS, regardless of preexisting condition. Within each treatment arm, AEs were similar regardless of preexisting condition.